Computer Games As Landscape Art - Nelson, Peter. author. aut Link
XI, 201 p. 45 illus.
Keywords: This book makes a significant contribution to the critical literature in game studies, around questions of space in particular, and to game analysis more generally. Nelson addresses the medium specificity of games and game engines as well as teasing out aesthetic, philosophical and political-economic connections with landscape painting. This interplay of art history and digital media theory is innovative, deftly handled and productive. The book is also, importantly, an engaging and enjoyable read. –Dr Seth Giddings, Associate Professor of Digital Culture & Design Southampton Institute for Arts and Humanities, science and technology lead Winchester School of Art, University of Southampton This book proposes that computer games are the paradigmatic form of contemporary landscape and offers a synthesis of art history, geography, game studies and play. Like paint on canvas, the game engine is taken as the underlying medium, and using the Valve Source Engine as the primary case study, it analyses landscapes according to the technical, economic and cultural features this medium affords. It presents the single-player first-person shooter (Half-Life 2) as a Promethean safari, examines how the economics of gambling and product placement shaped the eSports landscapes of Counter-Strike and reveals how sandboxes such as Garry’s Mod visualise the radical landscape of Web 2.0. This book explores how our relationship to the environment is changing, how we express this through computer games and how we can move beyond examining artistic influences on games to examining how historical connections flow through games and the history of landscape images. Peter A C Nelson is an artist and academic, originally trained in painting, drawing and art history, who publishes on computer games, graphics and aesthetics. He is currently an Assistant Professor at HongKong Baptist University.